Carotenoid content and composition in 20 medicinal plant species of traditional Malay midwifery postnatal bath - Othman, Rashidi; Abdul Halim, Siti Farah Aliyah; Mohd Hatta, Farah Ayuni; Jamaludin, Mohd Aizat (Lifescience Global, 2017)
Today in Malay community, midwifery traditional knowledge of herbal medicine has disappeared and extinct. The facts are Malay midwives are becoming rare and the more crucial is medicinal plants are over-harvested. The aim of this research is to identify and investigate the active pharmaceutical ingredients content in 20 selected species used in the Malay traditional bath. There is a solid need to analyse the potential of these natural bioactive compounds,particularly carotenoids to be fully utilised and commercialised especially in halal market and health advantages.Through High performance liquid chromatography (HPLC) analysis, all 20 species were found to have at least four individual carotenoid pigments with a relatively high concentration of lutein and β-carotene and lower concentrations of zeaxanthin. Strobilanthes crispus (Pecah Kaca) leaf was detected to have the highest total carotenoid content (1546.80±283.45 μg/g DW) while Psidium guajava (Jambu Batu) shoot has the lowest total carotenoid content (112.9±82.2 μg/g DW). The significant outcome of the research was a new findings of new natural bioactive compound sources as health promoting agents which covers not only the Shariah requirement, but also safety aspects. Moreover, it will preserve the traditional knowledge of Malay traditional bath practices.